1997
DOI: 10.1039/a702632c
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Gold Reduction and Stripping Processes at Platinum, Rhodium, Iridium, Gold and Glassy Carbon Micro- and Macrodisk Electrodes

Abstract: The gold AuIII + 3e(-)-->Au0 reduction and Au0-->AuIII + 3e- oxidation stripping processes in dilute aqua regia electrolyte (0.1 M HCl + 0.32 M HNO3) were examined at platinum, rhodium, iridium, gold and glassy carbon disk electrodes. After ascertaining that the preferred material was platinum, the effect of electrode size was evaluated by using nine different platinum disk electrodes having diameters ranging from 2 to 2000 microns. The optimum analytical response was obtained with a 50 microns diameter platin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…These elements could be determined only after the glassy carbon electrode had been gold-plated [20]. Gold alone has been determined at the platinum electrode [21]. However, the copious deposition of Se-Au examined by the EQCM technique on the gold electrode inclined us to use quantitative voltammetry with a mixture of these elements at the glassy carbon electrode.…”
Section: Mol Lmentioning
confidence: 99%
“…These elements could be determined only after the glassy carbon electrode had been gold-plated [20]. Gold alone has been determined at the platinum electrode [21]. However, the copious deposition of Se-Au examined by the EQCM technique on the gold electrode inclined us to use quantitative voltammetry with a mixture of these elements at the glassy carbon electrode.…”
Section: Mol Lmentioning
confidence: 99%
“…Gold analysis is required in mining processes [22] and for gold recovery from electronic components. A wide range of electrode materials [23,24] and sizes [25] has been studied for gold detection.…”
Section: Introductionmentioning
confidence: 99%
“…This peak current can be attributed to the reduction of gold(III) species to gold(I). 17,19,33 The response on the screen-printed carbon electrode coated with poly-L-histidine (SPCE/PH) film is essentially the same. However, there is an increase in the peak intensity for both experiments (curve b), while a bigger increase is observed in the chloride medium.…”
mentioning
confidence: 85%
“…Because the levels of gold in the body fluids of patients receiving treatments are usually < 5 µg mL -1 , analytical methods for determinations of total gold and of intact drugs and their metabolites have required detectors which are sensitive to very low concentrations of gold. Literature [14][15][16][17][18][19] has shown that both gold(III) and gold(I) can be determined by electrochemical analysis, in general using chemically modified electrodes under stripping analysis conditions. The main problem with electrochemical stripping analysis of gold(III) is finding a working electrode onto which gold can be deposited for subsequent stripping.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation